KEANEKARAGAMAN JENIS VEGETASI MANGROVE DI DESA SUNGAI BAKAU BESAR LAUT KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Heri, Paulinus; Burhanuddin, Burhanuddin; Riyono, Joko Nugroho (Universitas Tanjungpura, 2020)
Sungai Bakau Besar Laut Village is one of the villages in the Sungai Pinyuh Districk that has mangrove forest. This research aims to obtain species diversity of mangrove vegetation in Sungai Bakau Besar Laut Village. The benefits of this research is expected to provide data the condition of mangrove forest vegetation and the environment data that be used for local government and related agencies management mangrove forest in this village. The method is survey and used for systematic pathways. The observation plot layed Purposive Sampling. The analysis of vegetation in this study made 4 lines that each line has length 200 meters and distance between the lines as far as 100 meters. Based on the results of the vegetation analysis found 8 species of vegetation and consists of 5 genera, namely Avicennia, Bruguiera, Rhizophora, Soneratia and Xylocarpus.Keywords: Mangrove forest, Species diversity, Sungai Bakau Besar Village